AUF-1 knockdown in mice undermines gut microbial butyrate-driven hypocholesterolemia through AUF-1–Dicer-1–mir-122 hierarchy - Das, Oishika; Kundu, Jayanta; Ghosh, Atanu; Gautam, Anupam; Ghosh, Souradeepa; Chakraborty, Mainak; Masid, Aaheli; Gauri, Samiran Sona; Mitra, Debmalya; Dutta, Moumita; Mukherjee, Budhaditya; Sinha, Surajit; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
This discourse probes the mechanistic molecular details of butyrate action in maintaining host-cholesterol balance. Hepatic miR122 being the most indispensable regulator of cholesterol metabolic enzymes, we studied upstream players of miR122 biogenesis in the presence and absence of butyrate in Huh7 cells and mice model. We showed that butyrate treatment caused upregulation of RNA-binding protein, AUF-1 resulting in RNase-III nuclease, Dicer-1 instability, and significant diminution of miR122. We proved its importance of AUF-1 and sequential downstream players in AUF-1-knock-down mice. We synthesized unique self-transfecting GMO (guanidinium-morpholino-oligonucleotides) linked PMO (Phosphorodiamidate-Morpholino Oligonucleotides)-based antisense reagent and injection of which in mouse caused near absence of AUF-1 coupled with increased Dicer-1 and miR122, and reduced serum cholesterol regardless of butyrate treatment indicating that butyrate acts through AUF-1. The roster of intracellular players was as follows: AUF-1-Dicer-1-miR122 for triggering butyrate driven hypocholesterolemia. To our knowledge this is the first report linking AUF-1 with cholesterol biogenesis.